Ultrabrief Screens for Detecting Delirium in Postoperative Cognitively Intact Older Adults. Issue 9 (19th August 2020) - Sillner, Andrea Yevchak; Ngo, Long; Jung, Yoojin; Inouye, Sharon K; Boltz, Marie; Leslie, Douglas; Marcantonio, Edward R; Fick, Donna M
Abstract : The authors' sought to develop an ultrabrief screen for postoperative delirium in cognitively intact patients older than 70 years undergoing major elective surgery. All possible combinations of one‐, two‐ and three‐item screens and their sensitivities, specificities, and 95% confidence intervals were calculated and compared with the delirium reference standard Confusion Assessment Method (CAM). Among the 560 participants (mean age, 77 years; 58% women), delirium occurred in 134 (24%). We considered 1, 100 delirium assessments from postoperative days 1 and 2. The screen with the best overall performance consisted of three items: (1) Patient reports feeling confused, (2) Months of the year backward, and (3) "Does the patient appear sleepy?" with sensitivity of 92% and specificity of 72%. This brief, three‐item screen rules out delirium quickly, identifies a subset of patients who require further testing, and may be an important tool to improve recognition of postoperative delirium. Abstract :